Natural dyeing and anti bacterial finishing of cotton fabric with extracts from Justicia schimperiana leaf extract: a step towards sustainable dyeing and finishing - Worku Tegegne; Adane Haile; Yirdawu Zeleke; Yohannes Temesgen; Haymanot Bantie; Siltanu Biyable (International Journal of Sustainable Engineering)
The use of non-toxic and eco-friendly natural dyes on textiles has received much attention due to the increased environmental awareness to avoid some hazardous synthetic dyes. In the present study, an eco-friendly approach was developed to impart colour and antibacterial properties to cotton fabrics dyed with Justicia schimperiana leaf extract as a non-toxic natural colourant. The solvent method of extraction and exhaust dyeing method was used for this study. Copper sulphate, ferrous sulphate, and alum were applied in a simultaneous -mordanting process as a mordanting agent. The effects of shade percentage, dyeing temperature, and dyeing time on the obtained colour strength of the fabrics were investigated. Optimisation of dyeing conditions was carried out using Box Behnken design of expert software. An optimum level of 3. 28 colour strength (K/S) was observed in the sample treated with a shade percentage of 50 (% o.w.f), 72 °C dyeing temperature, and 45 minutes of dyeing time. Antibacterial properties of treated fabrics were evaluated against common pathogenic bacteria, Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative). The results indicated the treated fabrics possessed desirable antibacterial properties. The washing and rubbing fastness of the dyed fabrics were also reported.